2016
DOI: 10.1038/cddis.2015.386
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 activity is required for MLKL oligomerisation and membrane translocation and the induction of necroptotic cell death

Abstract: Necroptosis is a caspase-independent form of regulated cell death that has been implicated in the development of a range of inflammatory, autoimmune and neurodegenerative diseases. The pseudokinase, Mixed Lineage Kinase Domain-Like (MLKL), is the most terminal known obligatory effector in the necroptosis pathway, and is activated following phosphorylation by Receptor Interacting Protein Kinase-3 (RIPK3). Activated MLKL translocates to membranes, leading to membrane destabilisation and subsequent cell death. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 73 publications
2
129
0
Order By: Relevance
“…Figure 3) [35]. These observations are in line with other studies which have shown that crucial regulators of necroptosis and autophagy are HSP90 client proteins whose degradation upon HSP90 inhibition interferes with the coordinate execution of these processes [4547]. …”
Section: Resultssupporting
confidence: 85%
“…Figure 3) [35]. These observations are in line with other studies which have shown that crucial regulators of necroptosis and autophagy are HSP90 client proteins whose degradation upon HSP90 inhibition interferes with the coordinate execution of these processes [4547]. …”
Section: Resultssupporting
confidence: 85%
“…A recent report suggests that Hsp90 can modulate the stability of the RIPK3/MLKL complex and the oligomerization of MLKL and that an Hsp90 inhibitor can protect against Necroptosis[31]. To confirm that cpd 1 is not acting through Hsp90 inhibition, we compared the thermal stability of the Hsp90α catalytic domain bound to a positive control compound 17-AAG vs. cpd 1 .…”
Section: Resultsmentioning
confidence: 99%
“…12 Taken together, these studies led us to hypothesize that cell type-specific factors, such as proteins that modulate MLKL activation and 4HB domain exposure, oligomerization, membrane translocation and permeabilization are necessary for MLKL 4HB domain-induced cell death (summarized in Figure 6a). The identities of these proteins (termed X1-X4 in Figure 6a) are of enormous interest to the field and we have recently identified one such factor, the co-chaperone system Cdc37-HSP90, as an important mediator of MLKL activation, 23 which can be considered as putative X1 proteins. In addition, we have shown that phosphorylation of the MLKL activation loop coincides with MLKL oligomerization and membrane translocation but that these events precede membrane permeabilization by several hours, 15 again strongly implying that this is a regulated, rate-limiting stage in MLKL killing and imply the existence of X4 factors.…”
Section: Discussionmentioning
confidence: 99%